تصنیف النماذج المفسرة للضغوط المهنیة - ouaoua, Salahadinne (Finance and Business Economies Review, 2018)
Occupational stress poses a threat to people's health and in the same time on institution' s health. Stress from an institutional perspective is a very important phenomenon that can jeopardize the health of individuals and lead to physical, psychological and even social dysfunction. Occupational stress is of paramount importance in psychological research and has been presented as one of the health concerns of individuals in the 20th century by the World Health Organization (WHO); it was later classified as one of the most prevalent epidemics of the same organization. In this paper we will present a conceptual structure of stress, and then review the five major theories of occupational stress (Taxonomy of Stress Theories). Classifications are useful tools to simplify and organize our thinking about issues and events. Classification provides us a thinking structure to impose framework and meaning of the complexity. In so doing, the classifications should simplify matters only as much as they are required and no more, and should remain open for review and amendment.